Technical Vocabulary in Aviation: A Study of Private Pilot Students in Iceland - Andrés Páll Baldursson 1990- (2017)
Communication in aviation is of vital importance. A large number of all aviation incident reports worldwide are the result of miscommunication. By standardizing phraseology and vocabulary used by pilots and air traffic control (ATC), communication can become safer and more efficient. Aviation personnel can, however, not only rely on phraseological knowledge as there needs to be underlying language proficiency that supports the user, especially in unforeseen circumstances. English is the international standard language in aviation. The International Civil Aviation Organization (ICAO) has set certain language proficiency requirements (LPRs) to set strict English proficiency guidelines for aviation personnel to adhere to. Pilots and ATC need to learn and use complex technical vocabulary that is confined to aviation. This highly technical aviation vocabulary can be hard to master and there are various methods in teaching it. This essay examines the vocabulary proficiency of private pilot students in an aviation academy in Iceland. It attempts to find correlations between prior education and own perception of language proficiency, with vocabulary ability. Twenty students, enrolled in a 220-hour theoretical Private Pilot License (PPL) course took part in the study. They answered a simple questionnaire about themselves and two vocabulary tests, one based on the academic word list (AWL) and the other on aviation vocabulary (AVT). The students scored lower than expected on both tests, scoring 47% and 59% respectively on average. Many students would not have passed the LRPs in vocabulary knowledge. The low scores on the AVT can be attributed to two external factors, shortage of flight instructors in the practical portion of the PPL program and to a move of operations. There is no link between prior education and scores in the sample, but own perception of proficiency does correlate to scores on both vocabulary tests. Keywords: Aviation vocabulary, academic word list, phraseology, technical vocabulary, private pilot.